Imperial Desire : Dissident Sexualities And Colonial Literature - Ruppel, Richard R., 1953-; Holden, Philip, 1962- (Book collections on Project MUSE., 2003)
An exploration of the intersection of colonialism and homosexuality in fiction and travel writing, this volume brings together two dynamic fields of academic inquiry: colonial discourse analysis and queer theory.